Observation of multiferroicity in GaFeO3 by Mössbauer spectroscopy. (18th March 2015) - Nakamura, S; Kobayashi, Y; Kitao, S; Seto, M; Fuwa, A
Abstract: The multiferroic nature of GaFeO3 has been examined by 57 Fe Mössbauer spectroscopy in applied magnetic field. The spectra were analyzed as superposition of three subspectra corresponding to Fe 3+ ions on Fe1, Fe2, and Ga2 sites. The quadrupole coupling constants e 2 qQ /2 are about twice of the calculated values, which may be partially due to the spin-orbit interaction. At 4.2 K, e 2 qQ /2 of Fe1 and Fe2 sites increase noticeably when the magnetic field is applied along the c -axis. This is suggestive of the displacement of Fe ions toward - b direction. On the other hand, the increase of e 2 qQ /2 is not observed when the magnetic field is applied along the b -axis. These features seem to be related to the toroidal moment. An increase of hyperfine field of Fe1 site is observed when the magnetic field is applied. This may be also related to spin-orbit interaction.